The Influence of Education Level and Parenting Type on The Psychosocial Development of Preschool Children - Puridawaty, Brigita (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to analyze the effect of education level and parenting patterns on the psychosocial development of preschool children. Research and data collection were conducted at KB-TK Daru'l Hikam Cirebon City, with the research subject being one of the parents of kindergarten students of KB-TK Daru'l Hikam Cirebon City as many as 136 respondents. The instrument used was a questionnaire for data on education level, parenting patterns and psychosocial development of preschool children who asked for answers from parents. This study used an observational design with a cross sectional approach, with proportional purposive random sampling. Testing the presence or absence of influence between the level of education and type of parenting on the psychosocial development of preschool children was tested with binary logistic regression analysis. The results showed that there was an influence between the respondent's education level and the child's psychosocial development where the ρ value (0.000) < α (0.05) was obtained, the type of parenting pattern had an influence on the psychosocial development of preschool children where the ρ (0.000) < α (0.05) was obtained. When tested together between the level of education and the type of parenting pattern on the psychosocial development of preschool children, the level of education does not affect the psychosocial development of preschool children where ρ (0.159) > α (0.05) is obtained, but the type of parenting pattern affects the psychosocial development of preschool children where the test results obtained ρ (0.000) < α (0.05).